Factors associated with self-medication against COVID-19 in users of social networks - Peru. - Junchaya Yllescas , Vilma Amparo (2022)
Objective: To identify the factors associated with self-medication with drugs related to COVID-19 in the population using social networks - Peru. Material and Methods: A cross-sectional study was carried out in a purposive sample of 1068 users of Facebook in Peru, applying the survey technique to obtain data and the instrument was a Google digital questionnaire that considers the economic and cultural dimension.   Results: The predominant sociodemographic characteristics were found to be female 82.4 %, 18 to 22 years old in 28.3 %, university education in 57.8 %; also, as findings of economic factors, 34.8 % are of professional occupation, of regular economic income in 39.5 %, they are considered of average economic condition in 64.8 % and as cultural factors 84.3 % self-medicate, in frequency of rarely in 65 % and they do it on the recommendation of health personnel in 47.1 %.  Conclusion: Self-medication was high in Facebook-Peru users and it is significantly related to a greater number of cultural factors such as: sources for self-medication, the reasons and frequency of consumption is what predominates most in Facebook-Peru users, constituting a serious public health problem.